(untitled) (Journal of Health, Population and Nutrition, 2013)
This cross-sectional study assessed the current situation of and factors associated with consumption of diabetic diet among 399 type 2 diabetes mellitus (T2DM) subjects from Ahmedabad, Western India. The study was performed with diagnosed (at least one year old) diabetic subjects who attended the Department of Diabetology, All India Institute of Diabetes and Research and Yash Diabetes Specialties Centre (Swasthya Hospital), Ahmedabad during July 2010November 2010. The subjects completed an interviewer- administered questionnaire. The questionnaire included variables, such as sociodemographic factors, family history of diabetes, behavioural profile, risk profile (glycaemic status, hypertension, and obesity), and diet-related history (consumption of diabetic diet, consumption of low fat/skimmed milk, method of cooking, and sources for diet advice). Blood pressure, body mass index, glycosylated haemoglobin (HbA1c) level, and fasting lipid profile were measured. All analyses including multivariate logistic regression were conducted using SPSS, version 11.5. In total, 399 T2DM subjects (65% male, 35% female) with mean age of 53.16±7.95 years were studied. Although 73% of T2DM subjects were consuming diabetic diet, the good glycaemic control (HbA1c level <7%) was achieved only in 35% of the subjects. The majority (75%) of the subjects had a positive family history of diabetes, and 52% were obese. In 77%, the main source of dietary advice was doctor. In 36%, the main methods of cooking were: boiling and roasting. The final multivariate model showed that visit to dietician, level of education, intake of low fat, and family history of diabetes were independent predictors for diabetic diet consumption among T2DM subjects. However, longitudinal and cohort studies are required to establish the association between consumption of diabetic diet and glycaemic control. DOI: http://dx.doi.org/10.3329/jhpn.v30i4.13328 J HEALTH POPUL NUTR 2012 Dec;30(4):439-446